(untitled) (INNOVATIVE ECONOMY, 2025)
Nianko L.Yu., Dovbush A.V. DEVELOPMENT OF BANKING SERVICES IN THE CONDITIONS OF DIGITALIZATION: CHALLENGES, TRENDS AND PROSPECTS Purpose. The aim of the study is to conduct a comprehensive analysis of the transformation processes of banking services in the context of digitalization, in particular to identify key trends and outline the prospects for further development of the banking sector based on the implementation of digital technologies and FinTech solutions. Methodology of research. The methodological basis of the study is the dialectical method of scientific knowledge and a systematic approach. In the course of the study, a set of scientific methods was used to analyse the development of the banking system and its digitalization, in particular: analysis and synthesis, analytical – when processing literature sources; statistical analysis – to assess the dynamics of the banking system’s development and its digitalization, evaluate global trends, and identify key areas for digitalization implementation. The use of trend analysis made it possible to identify the main factors influencing the development of the banking system and its digitalization. The graphical method was used to visualize statistical data and trends, which provides a more visual representation of the dynamics of the banking system and simplifies the interpretation of the obtained results. Findings. The issues of digitalization of the banking system are studied. The level of penetration of online banking, the dynamics of launching new banks in the world, the number of digital banks in the world, and the number of clients of the world’s leading digital banks are determined and estimated. The list of promising and newest financial technologies in the banking sector is specified. Originality. The study proves that the prospects for the introduction of such digital financial technologies as artificial intelligence (AI), open banking, central bank digital currencies (CBDCs), biometric identification services, and green banking are directly related not only to their technological convenience but also to the level of government support and promotion of financial inclusion. This, unlike existing approaches, makes it possible to comprehensively assess not only the innovative potential of technologies but also their systemic integration into the banking model. It is established that DeFi (decentralized finance), despite the limited regulatory environment and high risk, can be further developed through gradual integration with traditional banking instruments, in particular through models of sharing APIs and smart contracts within hybrid financial systems. The study also improves the classification of the main risks that accompany the implementation of FinTech solutions in the banking sector by identifying strategic, technical, regulatory, organizational, and infrastructure threats. This allows for a more effective risk management model for the digital transformation of the bank. Practical value. The substantiated results of the study can be used to assess the trends in the implementation of FinTech solutions in the banking sector, to understand the role of FinTech in the strategic management of the bank, which allows considering digital innovations not only as tools for improving efficiency, but also as factors in the formation of long-term competitiveness. The study also improved the classification of the main risks accompanying the implementation of FinTech solutions in the banking sector by identifying strategic, technical, regulatory, organizational, and This allows for a more effective risk management model for the digital transformation of the bank. Key words: bank, banking services, digitalization, online banking, blockchain, Open Banking, digital transformation, FinTech.